Propuesta para el control y seguridad de la información de la empresa de ventas en Línea Buy Now aplicando Norma ISO 27001 - Camposano Monar, Galo Miguel (2020)
This project to implement control and computer security as well as risk analysis to the company, for Online sales. It is necessary to use the ISO 27001 Standard, which is responsible for implementing key strategies and commitments in order to protect the full and total information of assets and liabilities by applying communication and entrepreneurship as Sublines Networks and intelligent software and hardware technologies. The Online Buy Now company is located on Avenida Universitaria between Calle la third and fourth transversal of the city of Babahoyo, Los Ríos Province, Republic of Ecuador. Computer Security Audit Service carried out by external professionals aims to discover possible vulnerabilities after exhaustive reviews of software, communication networks, servers, workstations, mobile devices, etc. Importance of Computer Audit Computer systems are especially vulnerable to attack by malicious users. ISO 27001 standard It is an international standard, it allows the assurance, confidentiality and data integrity of the information, as well as the systems that process it. Benefits Benefits Disseminated recognition ISMS can request an Audit from an accredited entity to obtain the legitimacy of the internal controls system complies with the requirements of Corporate Management and business continuity. Certification: 1. Create training standards. 2. Selection of the standard. 3. Business support. 4. Assessment and Observation. 5. Certification to the operational IT process. SGSI  Reliability.  Probity.  Reservation. Objective Implement and maintain a convenient, positive and organized environment that allows you to preserve your information assets. Methodology Quantitative investigation. Exploratory investigation. Research techniques. Instrument. 1.1 Population and simple Organization is very limited, it was decided to survey all staff. Results In graphics.